Development of modified MCM-41 catalyst system towards epoxidation of 1-octene and Methyl Oleate / Suhaila Mohamed - Mohamed, Suhaila (2012)
The discovery of mesoporous molecular sieves has created a tremendous interest in the synthesis of these materials, particularly MCM-41 and its analogue, because of their very high surface areas and possibility of precisely tuned pore sizes (20-100 Å). These mesoporous materials have a wide range of potential applications starting from selective adsorption to heterogeneous catalysis, particularly for bulky molecules. Ti-MCM-41 has been widely developed as a catalyst for olefin epoxidation because of the active sites of Ti can acts as a very reactive compound for this reaction besides MCM-41 plays an important role as a support which is in the mesopore range. The research done provides an optimal reaction condition for epoxidation of Methyl Oleate using Ti-MCM-41 samples, based on the study of epoxidation of model compound, 1-Octene. The optimized reaction conditions lead to a maximum of epoxide selectivity and yield and also alkene conversion. In this study, a series of mesoporous titanosilicate Ti-MCM-41 molecular sieves with various Si/Ti ratios, 25, 55, 66, 80 and 100 have been hydrothermally synthesized at 100OC for 48 hours, using surfactant namely hexadecyl-trimethylammonium bromide as template and tetramethylammonium hydroxide as mineralizer. Chemical and physical properties of products obtained were characterized using powder X-ray diffraction (XRD), FTIR spectroscopy, DRUV-visible spectroscopy, nitrogen sorption measurements, differential thermal analysis (TGA-DTG), and scanning electron microscopy (SEM). XRD analysis shows that Ti-MCM-41 is a semicrystalline material with ordered mesoporous hexagonal structure which is indicated by a reflection peak at 2θ in the range of 1.6˚ to 2.6˚. The crystallinity of Ti-MCM-41 after calcinations was almost two-fold higher than that of the as-synthesized one. Calcination in nitrogen leads to desorption of organic templates from the pores of Ti-MCM-41 in contrast to template burning in air. The crystallinity and surface area of Ti-MCM-41 both decrease with an increase of titanium content. Nitrogen sorption measurements exhibit BET surface area of Ti-MCM-41 are in the range of 880 m2g-1 to 1075.163 m2g-1. Quite high BET surface areas with isotherms of type IV of the samples are typical for hexagonal MCM-41 type ordered mesoporous materials. The results of XRD and FTIR show that the solid products have the MCM-41 structure and contained only atomically dispersed titanium, consistent with framework titanium in Ti-MCM-41. All of the materials had a uniform pore size distribution which is around 3.0 nm. DRUV-visible analysis shows that Ti-MCM-41 has two types of titanium species; one species is titanium isolated tetrahedral which is active to catalyze epoxidation of alkenes and the other is titanium isolated octahedral. Catalytic activities of Ti-MCM-41 were tested in the epoxidation of 1-Octene and methyl oleate using tert-butyl hydroperoxide as peroxide in a batch reactor. Catalyst with high titanium content (Si/Ti = 25) is prone to deactivate due to high side compounds although at one hand, the hydrophobicity is improved. The titanium sites in MCM-41 catalysts are buried on the silica walls, being non-accessible to the reactants, thus lower the catalytic activity and turnover. The best is to use catalysts with average amount of titanium (Si/Ti = 80). When comparing between silylated and non-silylated samples, it was found that silylated samples exhibit higher catalyst activity, and the conversion and TON increased three times as compared to non-silylated samples. Silylation increases greatly the hydrophobicity of Ti-MCM-41 catalysts and therefore, water concentration on the surface of catalyst is reduced, and subsequent glycol formation which is one of the side products is nearly avoided. Silylation also decreases the number of silanol groups (and very probable Ti-OH groups) in the catalyst whereby these groups posses a weak acid character, but strong enough to catalyze the undesired reaction of oxirane ring opening.